Sleep in the Intensive Care Unit: Strategies for Improvement - Dorsch, Jennifer J.; Martin, Jennifer L.; Malhotra, Atul; Owens, Robert L.; Kamdar, Biren B. (Seminars in Respiratory and Critical Care Medicine, 2019)
Sleep in the intensive care unit (ICU) is considered to be subjectively poor, highly fragmented, and sometimes referred to as “atypical.” Although sleep is felt to be crucial for patient recovery, little is known about the association of sleep with physiologic function among critically ill patients, or those with clinically important outcomes in the ICU. Research involving ICU-based sleep disturbance is challenging due to the lack of objective, practical, reliable, and scalable methods to measure sleep and the multifactorial etiologies of its disruption. Despite these challenges, research into sleep-promoting techniques is growing and has demonstrated a variety of causes leading to ICU-related sleep loss, thereby motivating multifaceted intervention efforts. Through a focused review of (1) sleep measurement in the ICU; (2) outcomes related to poor sleep in the ICU; and (3) ICU-based sleep promotion efforts including environmental, nonpharmacological, and pharmacological interventions, this paper examines research regarding sleep in the ICU and highlights the need for future investigation into this complex and dynamic field.
Keywords: sleep; intensive care; critical care; delirium